Wireless Transmission of Data and Implementation of SDR - B.Amutha, R.Jeya, M.V. Jayanthkrishna Reddy, G. Preetam Prasad (International Journal of Advanced Science and Technology, 2020)
Software defined Radio (SDR) is the most recent method and one of the most significant remote interchanges in present-day times. SDR is fundamentally a radio which can be tuned to any frequency that underpins equipment. Furthermore, actualize diverse modulation and demodulation plots by reconfiguring the equipment and programming segments. Here this paper gives a nitty-gritty examination of SDR based radio beneficiaries that can be actualized by utilizing RTL-SDR. The execution of this SDR is finished by utilizing MATLAB, Simulink. The RTL-SDR is the minimal effort gadget with astounding utilitarian capacities the has diminished the general expense as it were.